Overexpression of stress granule protein TZF1 enhances salt stress tolerance by targeting ACA11 mRNA for degradation in Arabidopsis - He, Siou-Luan; Li, Bin; Zahurancik, Walter J.; Arthur, Henry C.; Sidharthan, Vaishnavi; Gopalan, Venkat; Wang, Lei; Jang, Jyan-Chyun (Frontiers in Plant Science, 2024)
Tandem CCCH zinc finger (TZF) proteins play diverse roles in plant growth and stress response. Although as many as 11 TZF proteins have been identified in Arabidopsis, little is known about the mechanism by which TZF proteins select and regulate the target mRNAs. Here, we report that Arabidopsis TZF1 is a bona-fide stress granule protein. Ectopic expression of TZF1 (TZF1 OE), but not an mRNA bindingdefective mutant (TZF1 H186Y OE), enhances salt stress tolerance in Arabidopsis. RNAseq analyses of NaCl-treated plants revealed that the down-regulated genes in TZF1 OE plants are enriched for functions in salt and oxidative stress responses. Because many of these down-regulated mRNAs contain AU-and/or U-rich elements (AREs and/or UREs) in their 3'-UTRs, we hypothesized that TZF1-ARE/URE interaction might contribute to the observed gene expression changes. Results from RNA immunoprecipitation-quantitative PCR analysis, gel-shift, and mRNA half-life assays indicate that TZF1 binds and triggers degradation of the autoinhibited Ca 2+ -ATPase 11 (ACA11) mRNA, encoding a tonoplast-localized calcium pump that extrudes calcium and dampens the signal transduction pathways necessary for salt stress tolerance. Furthermore, this salt stress-tolerance phenotype was recapitulated in aca11 null mutants. Collectively, our findings demonstrate that TZF1 binds and initiates degradation of specific mRNAs to enhance salt stress tolerance.